Identification and analysis of expressed sequence tags present in xylem tissues of kelampayan (Neolamarckia cadamba (Roxb.) Bosser) - Wei-Seng, Ho; Shek Ling, Pang; Julaihi, Abdullah (Springer, 2014)
The large-scale genomic resource for kelampayan was generated from a developing xylem cDNA library. A total of 6,622 high quality expressed sequence tags (ESTs) were generated through high-throughput 5’ EST sequencing of cDNA clones. The ESTs were analyzed and assembled to generate 4,728 xylogenesis unigenes distributed in 2,100 contigs and 2,628 singletons. About 59.3 % of the ESTs were assigned with putative identifications whereas 40.7 % of the sequences showed no significant similarity to any sequences in GenBank. Interestingly, most genes involved in lignin biosynthesis and several other cell wall biosynthesis genes were identified in the kelampayan EST database. The identified genes in this study will be candidates for functional genomics and association genetic studies in kelampayan aiming at the production of high value forests.